Governing passions peace and reform in the French kingdom, 1576-1585 - Greengrass, Mark, 1949- (Oxford University Press, 2007)
A re-evaluation of the central period in the French 'wars of religion', concentrating on the reactions of France's governing groups to these wars and drawing extensively on sources not hitherto examined to illuminate the sense of crisis that existed among the French governing elite at this time.